PENGARUH PEMBELAJARAN ONLINE DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI KELAS XII DI SMA N 2 MANDAU - Revi Murni Syari; Suarman Suarman; Hardisem Syabrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study aims to determine the effect of online learning and learning motivation on student learning outcomes in economics class XII at SMA N 2 Mandau. The sample in this study were students of class XII social studies at SMAN 2 Mandau for the academic year 2021/2022 which consisted of 5 classes with a total of 117 students using the slovin technique. Data were collected using questionnaires and documentation which were then analyzed using multiple linear regression. Based on the research, it was found that online learning and learning motivation had a positive and significant effect on student learning outcomes in Economics class XII Social Studies at SMA N 2 Mandau. So online learning and learning motivation together will improve student learning outcomesKeywords: Online Learning, Learning Motivation, Learning Outcomes.